2023
DOI: 10.1029/2023jd038530
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution CCAM Simulations Over New Zealand and the South Pacific for the Detection and Attribution of Weather Extremes

Abstract: Detection and attribution experiments are designed for the causal diagnosis of features in the climate system, including trends in mean climate and extreme events. While several detection and attribution data sets now exist, the coarse resolution of the climate models used (∼100‐km) often hinders their application to topographically complex regions like Aotearoa New Zealand and small island nations. The coarse atmospheric resolution may also be detrimental for simulating certain features of the atmospheric cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 107 publications
0
1
0
Order By: Relevance
“…However, most research has used CCAM as an RCM to downscale atmospheric data with coarser resolutions over a particular region based on global simulations with spatially varying resolutions. Recently, Gibson et al (2023) evaluated CCAM as an AGCM in simulating New Zealand weather and climate. Their results showed that CCAM performed particularly well at simulating the variability and extremes of temperature and precipitation over New Zealand.…”
Section: Hosted Filementioning
confidence: 99%
“…However, most research has used CCAM as an RCM to downscale atmospheric data with coarser resolutions over a particular region based on global simulations with spatially varying resolutions. Recently, Gibson et al (2023) evaluated CCAM as an AGCM in simulating New Zealand weather and climate. Their results showed that CCAM performed particularly well at simulating the variability and extremes of temperature and precipitation over New Zealand.…”
Section: Hosted Filementioning
confidence: 99%
“…Our RCM emulator was trained using predictor and target variables from the Conformal Cubic Atmospheric Model (CCAM), a global non-hydrostatic atmospheric model with a variable-resolution cubic grid (Chapman et al, 2023;Gibson et al, 2023;McGregor & Dix, 2008;Thatcher & McGregor, 2009). In contrast to commonly used RCMs like the Weather Research and Forecasting Model (WRF), which rely on lateral boundary conditions from reanalysis or CMIP6 GCMs, CCAM is run as a global variable-resolution model (McGregor & Dix, 2008).…”
Section: Regional Climate Model Configurationmentioning
confidence: 99%
“…CCAM is run globally with spectral nudging to input fields from GCM atmospheric variables. A detailed evaluation of CCAM is presented in Gibson et al (2023) for this region, which used a very similar version of CCAM (i.e. model grid and physics configuration).…”
Section: Regional Climate Model Configurationmentioning
confidence: 99%
See 1 more Smart Citation